Kebermanfaatan Mata Kuliah Pengauditan Bagi Mahasiswa Akuntansi terhadap Kemampuan Mendeteksi Fraud - Cici Girik Allo; Agus Nisfur Romdioni (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
The aim of this research is to determine the influence of accounting students' perceptions of the benefits of audit courses on their ability to detect fraud in Merauke City. The benefit for accounting students who will become auditors in the future, this research will help identify the extent of fraud early on. The method used in this research is empirical research using a quantitative approach. The sample was 4th semester students who had taken courses at a university in the city of Merauke. The results of the research, namely a descriptive analysis of accounting students' perceptions carried out among university students in Merauke City, show that the perceptions of accounting students in Merauke City have a significant influence on the benefits of higher education audit courses. The implementation of a whistleblowing system for students is very helpful in reducing incidents of fraud in the academic and non-academic sectors as preparation for those who will become examiners or auditors in the future in pursuing the Public Accounting profession.